Podcasts: Improving Students’ Extensive Listening Skills - R Dwi Arifa Camelia; Maulana Yusuf Aditya; Arfiyan Ridwan (English Teaching Journal : A Journal of English Literature, Language and Education, 2021)
Podcasts is one of the technologies that can be used as an effective media to teach students’ listening skill, especially extensive listening. This research aims to know the effectiveness of using podcasts application in teaching extensive listening. The method in this study used quantitative research. The design of this research was pre-experimental one group pre-test and post-test design. It involved the Eleventh Grade Students of SMA Negeri 2 Bangkalan as the subject of the research. In this research, the data were obtained toward the results of listening tests. The research was started by giving pre-test, treatments, and post-test to experimental group. The data of the tests were analyzed by using Paired Sample T-Test. The results showed the significant difference between pre-test and post-test, It indicate that the value of significance (Sig. 2-tailed) is 0.002 lower than 0.05. The results of the statistical hypothesis testing showed that the P-value lower than α (0.002<0.05), it means that Ha was accepted and Ho was rejected. It can be concluded that podcasts application is effective and brilliant media that can be suggested to be used on teaching listening.